INKONSISTENSI PRINSIP TIME VALUE OF MONEY DALAM OPERASIONAL TRANSAKSI KEUANGAN SYARIAH DAN SOLUSINYA - Siti Mujibatun (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2016)
The concept of Time Value of Money in the LKS is not accepted because of riba, but in practically mainly on small investors to invest, will face a big problem if it rejects the principle of Time Value of Money, whenever any country will have inflation. will be injustice when Islamic banking do not give a rate of return to the investor. The research is a qualitative, primary data sources and data collection consisted of a document. The Brochure of Product Financing Transactions in LKS, b). Fatwa DSN-MUI 2000, c). CD-ROM File Maushu'ah al-Hadith al-Sharif al-Tis'ah 1997 Edition II, d). The Books related to the concept of Time Value of Money, e). SOP (Standard Operational Product) financing and acounting system. Secondary data consists of various books related to the concept of Time Value of Money both modern and classical fiqh books and Research results related to this research problem. This research analyzes the discriftive approach, with results as follows: 1. Time Value of Money in the LKS is not acceptable, because the increase in the Time Value of Money earned should be of real business, not because of the debt contract / qardh 2. Time Value of Money by economic concepts Hadis Muhammad saw among other things contained in the contract of salam/ indent, BBA and 'disconto, araya and provision for debt payments 3. the occurrence of in-consistency between ideology Time Value of Money with praxis in LKS due in addition to not paying attention to the business logic of the Prophet, helplessness in operating system usage still based on the operating system Conventional Financial Institutions (LKK).